Urgensi Pendidikan Seks Pada Remaja Autis - Septylia Nugraheni; Naimatus Tsaniyah (Institut Agama Islam Negeri Palopo, 2020)
This study discusses sex education for autistic adolescents. The method used is the liberary reseach method, the data discussed inclused characteristics of autistic person, autism in Islam, puberty of autistic adolescents, psychosexual development in autistic adolescents, material and methods of sexual education for autistic adolescents, prevention and treatment, the role of care giver in educating autistic individuals, as well as in relation to the verses of the koran. This study concludes that autistic adolescents also need sex education to make them whole and independent human beings. As well as preventing sexual harassment and deviant behavior caused by the inability of autistic individuals to respond or express sexual urges they feel during puberty. The purpose of this paper is to provide an understanding of the importence of sexuality education for autistic adolescents, so as to avoid things that are contrary to the norms prevailing in society or religion, and to make autistic individuals independent and mode respectful of themselve and other.